Measurement of B(t→Wb)/B(t→Wq) in top-quark-pair decays using dilepton events and the full CDF Run II data set. - Aaltonen, T; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Arisawa, T; Artikov, A; Asaadi, J; Ashmanskas, W; et al. (2014)
We present a measurement of the ratio of the top-quark branching fractions R=B(t→Wb)/B(t→Wq), where q represents any quark flavor, in events with two charged leptons, imbalance in total transverse energy, and at least two jets. The measurement uses proton-antiproton collision data at center-of-mass energy 1.96 TeV, corresponding to an integrated luminosity of 8.7  fb^{-1} collected with the Collider Detector at Fermilab during Run II of the Tevatron. We measure R to be 0.87±0.07, and extract the magnitude of the top-bottom quark coupling to be |V_{tb}|=0.93±0.04, assuming three generations of quarks. Under these assumptions, a lower limit of |V_{tb}|>0.85(0.87) at 95% (90%) credibility level is set.